Epidemiology and Spatial Distribution of Parasitic Infections in Cats in Malang, East Java, Indonesia: Risk Factors and Public Health Implications - Yesica, Reza; Pamungkas, Hafiz Bintang; Rahardja, Azzam Dhiya’ulhaq; Putri, Denissa Rachmawati Purnama; Kusumarini R, Shelly (Universitas Airlangga, 2025)
Cats are common companion animals that are susceptible to various parasitic infections, particularly under unsanitary environmental conditions. Apart from transmitting zoonotic infections, infected cats may also suffer from metabolic disorders, malnutrition, anemia, and even death. Fecal, hair, and ectoparasite samples from 170 cats (stray and domestic) were collected from 12 districts in Malang. Statistical tests (Chi-square, OR, and RR) and QGIS-based spatial mapping were employed for data analysis. The findings revealed that 46.4% (79/170) of gastrointestinal endoparasite cases involved Ancylostoma spp. (20.6%), Toxocara cati (19.4%), Toxascaris leonina (7.6%), Strongyloides spp. (2.9%), Dipylidium caninum (4.1%), Cystoisospora felis (5.8%), Cystoisospora rivolta (3.5%), and Toxoplasma gondii-like oocysts (1.1%). Ectoparasite infestations accounted for 52.9% (90/170), with Ctenocephalides felis (50.5%), Sarcoptes scabiei (3.5%), Felicola subrostratus (1.1%), and Rhipicephalus sanguineus (0.5%) being recorded. Risk factor analysis revealed a significant correlation (p < 0.05) between lifestyle and the prevalence rates of cat gastrointestinal endoparasite infections and ectoparasite infestations, while sex and altitude showed no significant correlation (p > 0.05) with either. The findings of the study bear significance for both human and animal health, highlighting the importance of interdisciplinary collaboration among preventive medicine, veterinary science, and public health, and providing a valuable evidence base to support policy development and targeted intervention programs aimed at controlling zoonotic parasites in companion animals, particularly in urban and peri-urban areas.